Environmental enrichment as a mitochondria-targeting systems strategy across neurodegenerative diseases and retinal dystrophies - Rusciano, Dario; Gagliano, Caterina; Avitabile, Alessandro; Maya-Vetencourt, José Fernando (Frontiers in Neuroscience, 2026)
Mitochondrial dysfunction is a central contributor to neurodegenerative disorders affecting both the central nervous system and the retina, where impaired energy metabolism, oxidative stress, and defective cellular resilience converge to drive progressive neuronal loss. Environmental enrichment (EE), a multimodal non-pharmacological paradigm, has emerged as a powerful modulator of brain and retinal plasticity in preclinical models, promoting adaptive responses that support mitochondrial function and neurotrophic signaling. This review synthesizes evidence indicating that EE influences mitochondrial quality control, redox homeostasis, synaptic resilience, and neuroimmune balance across a range of experimental models of neurodegeneration and retinal dystrophy. While these effects converge on shared downstream pathways, important disease-, cell-type-, and context-specific differences exist, and mechanistic generalization across systems requires caution. Human studies remain limited, heterogeneous, and often focused on functional outcomes rather than direct biological endpoints, resulting in modest and variable effect sizes. Rather than proposing EE as a stand-alone therapy, we frame it as a system-level, disease-modifying context that may enhance endogenous protective capacity and potentially complement pharmacological, genetic, or rehabilitative interventions, pending disease-specific validation. Forward-looking perspectives, including digitally mediated and AI-supported EE-inspired approaches, are discussed as conceptual strategies whose biological relevance will depend on future studies integrating functional outcomes with validated molecular and metabolic biomarkers. Together, the available evidence positions EE as a biologically grounded, non-invasive framework for promoting neuro- and retino-protective resilience, while underscoring the need for rigorously designed translational and clinical studies to define its therapeutic boundaries and mechanisms of action.